Penerapan Promotion Mix Pada Toko Star Light - Yandi Suprapto; Innzelyn Innzelyn (Universitas Internasional Batam, 2021)
The author carries out practical work activities at the Star Light Store which is located in the Aviari Pratama Complex block A2 no 3, Batu Aji - Batam. The purpose of carrying out this practical work activity is to help Star Light Store owners in solving the problems faced, namely relatively few consumers who come to shop so that the authors implement a promotion mix strategy that can attract customer attention to make purchases so as to increase sales figures. The efforts made by the author in increasing sales can be by creating attractive promotions for Star Light Stores. The promotion carried out by the Star Light Store had an impact in terms of sales figures, the existence of Star Light Store was increasingly recognized by the wider community, and many customers came to shop. The implementation of this practical work activity resulted in a promotional mix consisting of digital marketing, promotion, advertising, promotion ads, and e-commerce which seeks to help Star Light Store owners who have low sales figures due to a large number of competitors and promotional methods used. so far only by word of mouth.